Strengthening Cabinet Office Procedures - Goldsworthy, Diana (World Bank, Washington, DC, 2016)
Located at the hub of Government’s decision-making system, center-of-government offices are crucial to a government’s capacity to define and implement their policies and programs. The work of coordination can be complex and demanding, especially where conflicting political imperatives are involved; and where capacity in the center-of-government office is lacking. For both reasons, standard procedures are essential to create a reliable, non-controversial framework within which to deal with competing priorities and demands. The procedures may be basic and simple in the first instance, gradually becoming more sophisticated over time as capacity increases. This note describes some of the basic procedures being developed and introduced in the Prime Minister’s Office of the Kingdom of Tonga, which serves both the Prime Minister and the Cabinet. Although the procedures are tailor-made for Tonga, they are based on generic models that can be observed in many differing administrations.